Relação entre as alterações estruturais do cerebelo e os transtornos psiquiátricos - Baldaçara, Leonardo [UNIFESP] (2011)
Classically it was attributed to the cerebellum only functions regarding the control of movements, posture and balance. However, several studies have shown that the cerebellum also participates in the control of cognition, emotional processing and behavior through direct and indirect pathways. New evidence suggests that the cerebellum has structural and functional abnormailities in psychiatric disorders, including schizophrenia, mood, anxiety, attention deficit disorder with hyperactivity, and autism. In some cases, isolated findings are found in case reports, in others, in comparative studies, but with little control over confounding variables. In this research, the goal was to measure the volume of the cerebellum and its subregions in individuals with psychiatric disorders and to relate these findings to the symptoms. Patients with different degrees of cognitive impairment (Epidemiology of the Elderly - UNIFESP) and patients with post-traumatic stress disorder (PTSD) from population studies were analyzed. Also, patients with bipolar disorder from an outpatient clinic (Center for the Study of Mood and Anxiety Disorders, Universidade Federal da Bahia) were recruited for this study. Controls were individually recruited for each study and included on the analyses. All subjects underwent a 1.5T structural magnetic resonance scan. Images were analyzed by manual and semiautomatic delimitation of region of interest (ROI) methods. Volumetric measures and symptoms measurements, by psychometric scales, were performed and compared between patients and controls. The cerebellum volume is reduced in patients with cognitive impairment without dementia and with dementia, in patients with posttraumatic stress disorder, and in patients with bipolar disorder compared to controls. In dementia and posttraumatic stress disorder patients, the left cerebellar hemisphere and vermis volume are reduced. In bipolar disorder, volumes of both hemispheres and the vermis are reduced. In the first two studies, these cerebellar volumetric reductions correlated with symptoms of the disease. The exact nature of cerebellar involvement in mental processes is still not understood. However, structural neuroimaging techniques are valuable tools to study the contribution of the cerebellum in the pathophysiology of psychiatric disorders. Abnormalities in cerebellar structure and its functions have been reported in some of these diseases. Future researches with larger samples are still needed to clarify these findings and investigate whether they are important for the treatment and prognosis. Moreover, the study of cerebellar function may contribute to the emergence of new horizons for the neurosciences, including the identification of new subtypes of diseases and better understand the dynamics of neural circuits.